Salih Qaftan And The Process Of Kurdish Historiography In The Middle Centuries - Ahmad, Younis Mahmood; Ali, Nariman Abdalla (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research aims to explain the formation process of Kurdish historiography over the historical periods and especially in the middle centuries, being known as the Islamic period, and it is, hereby, attempted to investigate the role of Salih Qaftan, a famous Kurdish historiographer. Rewriting all historical periods of Kurdistan in Kurdish language is the most important feature and the most effective historical knowledge of historians of this period. This research is made up of three parts. The first part is dedicated to a summary of Salih Qaftan’s life and Kurdish historiography from his point of view. The second part explains the historiography method of Salih Qaftan, and the final part deals with some of this historian’s views regarding analyzing and interpreting Kurdish history..Key words: History, Kurdish historiography, historiography of the middle centuries, Salih Qaftan.